2003
DOI: 10.1029/2002ja009604
|View full text |Cite
|
Sign up to set email alerts
|

Martian hydrogen exosphere charge exchange with solar wind

Abstract: [1] Charge exchange of solar wind with the Martian exosphere has been shown to play a crucial role in the formation of the magnetic pileup boundary observed by Mars Global Surveyor. However, the question of how the Martian exospheric structure is quantitatively altered by charge exchange of the solar wind remains open. To answer this question, a three-dimensional Monte Carlo exosphere model was developed. In this model the effects of planetary rotation, photoionization, Lyman a scattering, and charge exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…For current solar conditions, this frequency, rescaled to the Sun‐Mars distance, is between 0.3 and 0.8 × 10 −7 s −1 and therefore the typical lifetime of an exospheric hydrogen atom is >115 days. The charge exchange ionization frequency estimated by Chen and Cloutier () is at most 1 order of magnitude larger (~5 × 10 −7 s −1 ), consistent with the escape rate ratio of H + produced by charge exchange and photoionization computed by Modolo et al (). This ionization frequency leads to a lifetime of ~20 days.…”
Section: Modeling Of the Lateral Transportsupporting
confidence: 86%
“…For current solar conditions, this frequency, rescaled to the Sun‐Mars distance, is between 0.3 and 0.8 × 10 −7 s −1 and therefore the typical lifetime of an exospheric hydrogen atom is >115 days. The charge exchange ionization frequency estimated by Chen and Cloutier () is at most 1 order of magnitude larger (~5 × 10 −7 s −1 ), consistent with the escape rate ratio of H + produced by charge exchange and photoionization computed by Modolo et al (). This ionization frequency leads to a lifetime of ~20 days.…”
Section: Modeling Of the Lateral Transportsupporting
confidence: 86%
“…The model applies a Chamberlain model for the density of H atoms above the exobase, excluding satellite particles. This approach was verified by Monte Carlo modeling by Chen and Cloutier [2003], who found that this approach accounts best for exosphere changes due to charge exchange with solar wind protons. The hydrogen density below the exobase is derived from the resolution of the diffusion equation for atomic hydrogen through a CO 2 atmosphere [Chaufray et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…However, the addition of a relatively small density of heavier ions causes the growth rate of the proton cyclotron instability to be significantly decreased and thereby allows the mirror instability to become the dominant mode in an anisotropic plasma [ Price et al , 1986]. Such a situation occurs in the Martian magnetosheath since the relatively large exosphere has been calculated to extend out to magnetosheath altitudes [e.g., Chen and Cloutier , 2003].…”
Section: Discussionmentioning
confidence: 99%